TUJUAN G-8 MEMBANTU NIGERIA DALAM MENCAPAI TARGET MILLENNIUM DEVELOPMENT GOALS (MDGs) 2015 - Hanifahturahmi "; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research explains the role of the G-8 countries to help developing countries achieve the Millennium Development Goals (MDGs), especially in alleviating poverty and other social problems in Nigeria. Nigeria is a rich country in oil and gas, but there are still many Nigerians who live on average below U.S. $ 1 per day. The perspective of this research is neo-liberalism. Neo-liberalism tends to be optimistic in looking at the mutual benefits obtained due to the interaction of state and non-state actors in globalization. The interdependence theory is used to analyze the foreign aid given by the group of rich countries to the developing countries who are willing to do a free market economy. This research uses qualitative methods with techniques of writing a literature review through secondary data already available from the literature. This research shows that the point of Partnership in the eight goals of the MDGs is helpful Nigeria. The G-8 helps Nigeria through Nigeria's foreign debt relief, especially to Nigeria's biggest creditor, namely the Paris Club. The G-8 effort for development in Nigeria has been discussed at the Gleneagles summit, Scotland. Besides double its ODA in 2010, the G-8 also assist in the education field, health, water and sanitation and infrastructure development to support the investment climate in Nigeria. If this situation continues to be supported by a system of government that is free from corruption and internal conflicts then Nigeria will be able to achieve the targets of the first goal until the seventh MDG goals by 2015.Keywords: Millennium Development Goals, Nero-liberalism, Global Partnership, Cooperation, Gleneagles.